CITRONELLA OIL AS BIOADDITIVES ON SI ENGINE PERFORMANCE CHARACTERISTICS - Alfian, Devia; Farhani, Amna Citra; Supriyadi, Didik; Prahmana, Rico Aditia; Silitonga, Dicky J (Jurnal Rekayasa Mesin, 2023)
Current dynamics of world energy supply have driven various innovations by the industry as well as research communities. Fossil fuels, although experiencing a declining interest due to sustainability issues, remain undeniably crucial since they are nearly irreplaceable in some sectors including electricity generation, it is necessary to continuously establish efforts to improve efficiency of those kinds of fuel. In this work, the authors evaluate the potential of locally sourced essential oils, namely citronella, as a fuel additive in a vision of raising the fuel economy of gasoline RON 90. Citronella oil was selected based on a positive hypothesis deduced from its chemical properties, as mentioned in multiple published works. Tests were made on a generator-set powered by gasoline engine using the mixture of RON 90 and citronella oil of various concentrations as the fuels. In addition, a commercial synthetic additive was also tested alongside the essential oil to provide a comparative figure. Meanwhile other investigators suggest a favorable effect of essential oils, our results show that citronella oil additions lead to higher fuel consumption at the same power level. A similar negative effect was also demonstrated by the synthetic additive. The only sector showing positive results is in terms of exhaust temperature where experiments with citronella additives create lower exhaust temperature as compared to pure gasoline and synthetic additives. However, rooms for innovation remain open by exploring other variables such as higher additive concentrations or combining different kinds of essential oils.